The phenomenon of Sexting among Spanish Teenagers: Prevalence, Attitudes, Motivations and Explanatory Variables - Gil-Llario, María Dolores; Morell-Mengual, Vicente; Giménez García, Cristina; Ballester-Arnal, Rafael (Anales de Psicología / Annals of Psychology, 2020)
Sexting is a recent phenomenon in which people send and receive photos, videos and/or text messages of sexual nature via smartphones or similar devices. Similar to other developed countries, it is becoming an increasingly popular practice among teenagers in Spain. Provided it has appeared very recently, scarce research has focused on examining in-depth factors involved in its initiation and maintenance. Therefore, the two main aims of this study were to determine its prevalence and to analyse the explanatory variables of the sexting behaviours. The sample consisted of 784 Spanish adolescents (52% boys and 48% girls) between 12 and 18 years of age (M = 14.44; SD = 1.61). The results showed that 24.4% have practised sexting at some time, with an average of 2.32 people (SD = 2.70). The regression analysis revealed that positive attitudes towards sexting, level of impulsivity, age, being male and having a partner are variables that predict engagement in sexting. These results are very important for designing and implementing preventive strategies that emphasise the responsible use of ICTs and social networks.